Patient-centered assessment of treatment for alpha-1 antitrypsin deficiency: literature review to identify concepts and measures for people with alpha1-antitrypsin deficiency - Ekin Seçinti; Karolina Schantz; Laure Delbecque; John Krege; Rikki Mangrum; Sarah E. Curtis (Orphanet Journal of Rare Diseases)
Abstract Background Alpha-1 antitrypsin deficiency (AATD) is a genetic disorder that can result in a range of illnesses, with chronic obstructive pulmonary disease (COPD) being one of the most common. Although some people obtain genetic testing that identifies AATD, many people are unaware that they have AATD until they develop COPD, often at a younger age than is typical. Treatment for AATD consists primarily of augmentation with AAT, requiring weekly infusions of blood products for most patients. This treatment can slow disease progression and improve symptoms, but is burdensome; thus, people with AATD could benefit from additional or alternate treatments. However, to guide the development of new treatments, researchers need to identify which outcomes matter to people with AATD. Methods We conducted a scoping literature review to better understand patient experiences with AATD and its treatment and identify patient-reported outcome measures (PROMs) used to assess symptoms and impacts in studies of people with AATD. Results The review identified 44 concepts related to symptoms and disease burden, grouped into six domains (symptoms, physical function, cognitive function, emotional function, psychosocial function, and treatment burden) and 24 PROMs that have been used in research on AATD. None of the identified measures were developed specifically for people with AATD. Research on patient-focused outcomes was limited, suggesting a significant gap in knowledge. Conclusions People with AATD experience a variety of disease-related burdens, but this study showed there is a lack of published, in-depth studies to support selection and evaluation of patient-centered outcomes among populations of people with AATD. A limited number of PROMs have been used in research on AATD or in clinical trials of treatment, including COPD-specific measures that assess symptoms and quality of life and measures of mood, sleep, and general physical and psychosocial functioning. The current study documented the available evidence and compiled a list of potential concepts of interest, but further qualitative and quantitative studies will be needed to understand the outcomes that matter to people with AATD and to evaluate the alignment between these outcomes and available measures.